2019
DOI: 10.1111/ijn.12777
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐informed policymaking: Modelling nurses' career pathway from registered nurse to advanced practice nurse

Abstract: Aim To formulate, validate, and disseminate policy, modelling nurses' career pathway from registered to advanced practice nurse. Method The evidence‐informed policy and practice pathway framework was utilized. Multiple methods were used, including scoping review of literature, consultation of key informants, survey study, and expert group round‐table discussions during 5‐year project between 2013 and 2018. Results Through (a) sourcing, (b) using, and (c) implementing the evidence, the expert group worked syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 28 publications
0
51
1
Order By: Relevance
“…Within Denmark, Iceland and Finland, the minimum CNS education is at the master's level which includes 90 to 120 European Credit Transfer System (ECTS) credits. (Jokiniemi et al, 2019; Studienaevnet for Sundhedsvidenskab, 2019; The Directorate of Health, 2019).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Within Denmark, Iceland and Finland, the minimum CNS education is at the master's level which includes 90 to 120 European Credit Transfer System (ECTS) credits. (Jokiniemi et al, 2019; Studienaevnet for Sundhedsvidenskab, 2019; The Directorate of Health, 2019).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Although the minimum training is a master's degree, there are no specific requirements or curriculum for CNS post-graduate programs which are between 90 and 120 ECTS. In addition, the CNS roles are not regulated, thus there is no title protection (Jokiniemi et al, 2019). Despite these challenges, a CNS subgroup was founded under the Finnish Association of Nurses in 2019 and the CNS competency development is well on its way with initial competency descriptions validated recently (Jokiniemi et al, 2018(Jokiniemi et al, , 2019.…”
Section: What Does This Paper Contribute To the Wider Global Clinical Community?mentioning
confidence: 99%
“…However, in many countries outside of North America, CNS competency development is in its early stages, and a lack of legislative and regulatory mechanisms or protected titles for CNS roles is evident (Jokiniemi et al, 2018;Maier et al, 2017). Among the examined countries, in Finland and Denmark there is no title protection for the CNS, although general guidelines do exist (Jokiniemi et al, 2019;Sundhedsstyrelsen, 2009). Iceland, in turn, has certified CNSs since 1993 (The Directorate of Health, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Findings suggested that public awareness of nursing image and family and religious influences would be captivated and could have an impact on the role of advanced nurses in Saudi Arabia. Accordingly, research suggested that the social image of nursing could affect the promotion of the nurse-patient relationship and thereby affect the advance role development of nurses [3]. Conversely, previous research indicated that implementing an advanced nursing role may improve the public perception and increase the nursing profession's reputation [33].…”
Section: Discussionmentioning
confidence: 99%
“…These barriers can be classified into either system-level or organizational-level barriers. The barriers at the system level include the absence of policy, guidelines, and regulations for the APN roles [2] [3]. Confusion about APN roles in healthcare settings, the scope of practice, use of different titles or terminology to describe nurse practitioners or advanced practice nurses, in addition to the absence of a recognized funding mechanism can impact the understanding of their role [4] [5] [6].…”
Section: Introductionmentioning
confidence: 99%